Vertical thermodynamic structure of the troposphere during the Norwegian young sea ICE expedition - Kayser, Markus; Maturilli, Marion; Graham, Robert M.; Hudson, Stephen R.; Rinke, Annette; Cohen, Lana; Kim, Joo-Hong; Park, Sang-Jong; Moon, Woosok; Granskog, Mats A. (Journal of Geophysical Research: Atmospheres, 2017)
The Norwegian young sea ICE (N-ICE2015) expedition was designed to investigate the atmosphere-snow-ice-ocean interactions in the young and thin sea ice regime north of Svalbard. Radiosondes were launched twice daily during the expedition from January to June 2015. Here we use these upper air measurements to study the multiple cyclonic events observed during N-ICE2015 with respect to changes in the vertical thermodynamic structure, moisture content, and boundary layer characteristics. We provide statistics of temperature inversion characteristics, static stability, and boundary layer extent. During winter, when radiative cooling is most effective, we find the strongest impact of synoptic cyclones. Changes to thermodynamic characteristics of the boundary layer are associated with transitions between the radiatively “clear” and “opaque” atmospheric states. In spring, radiative fluxes warm the surface leading to lifted temperature inversions and a statically unstable boundary layer. Further, we compare the N-ICE2015 static stability distributions to corresponding profiles from ERA-Interim reanalysis, from the closest land station in the Arctic North Atlantic sector, Ny-Ålesund, and to soundings from the SHEBA expedition (1997/1998). We find similar stability characteristics for N-ICE2015 and SHEBA throughout the troposphere, despite differences in location, sea ice thickness, and snow cover. For Ny-Ålesund, we observe similar characteristics above 1000 m, while the topography and ice-free fjord surrounding Ny-Ålesund generate great differences below. The long-term radiosonde record (1993–2014) from Ny-Ålesund indicates that during the N-ICE2015 spring period, temperatures were close to the climatological mean, while the lowest 3000 m were 1–3∘C warmer than the climatology during winter.